Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Is there any formula for the series below: $$ (2^0)n + (2^1)(n-1) + (2^2)(n-2) + (2^3)(n-3) + \cdots +(2^{n-1})(1) $$ If no, please let me know how to solve such series

share|cite|improve this question

Here are some tools to solve your problem.

  • The first basic observation, going back to Zeno, is that $\sum\limits_{k=1}^n2^{-k}=1-2^{-n}$.

  • More generally, for every $x$, $S_n(x)=\sum\limits_{k=0}^{n-1}x^{k}=\frac{x^n-1}{x-1}$ (watch out for the shift of indexation).

  • Differentiating this with respect to $x$, one gets a formula for $T_n(x)=\sum\limits_{k=0}^{n-1}nx^{n}.$

Now, you are interested in the sum $U_n(x)=\sum\limits_{k=0}^{n-1}x^k(n-k)$ (which is not a series, by the way) for $x=2$. Your first task is to express $U_n(x)$ in terms of some $S_n(x)$ and $T_n(x)$ defined above.

share|cite|improve this answer

Due to the symmetry, rewrite the sum as

$$\sum_{k=0}^{n} k \, 2^{n-k} = 2^n \sum_{k=0}^{n} k \, \left ( \frac{1}{2} \right )^k $$

You may use the fact that

$$\sum_{k=0}^{n} k \, r^k = \frac{r-r^{n+1}}{(1-r)^2} - n \frac{r^{n+1}}{1-r} $$

with $r=1/2$. The result is


share|cite|improve this answer

If you meant $$2^0(n)+2^1(n-1)+2^2(n-2)+\cdots+2^{n-2}(2)+2^{n-1}(1)$$

Let $$S=2^0(n)+2^1(n-1)+2^2(n-2)+\cdots+2^{n-2}(2)+2^{n-1}(1)$$

So, $$2S=2^1(n)+2^2(n-1)+2^3(n-2)+\cdots+2^{n-1}(2)+2^{n}(1)$$

So, $$2S-S=2^1\{n-(n-1)\}+2^2\{(n-1)-(n-2)\}\cdots+2^{n-2}(3-2)+2^{n-1}(2-1)+2^n-n$$


share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.